Optimizing the Health Dimension Program in the Human Development Index to Improve Human Resource Quality in the Kediri City - Muhammad 'Abid Yardan,; Endah Kurniawati, (Jurnal Manajemen, 2026)
The Human Development Index (HDI) is a vital indicator in measuring the success of regional development, and thru the health dimension, it plays a strategic role in improving the quality of human resources. Kediri City shows a positive trend, increasing from 78.78 in 2020 to 80.97 in 2023. However, it still faces health challenges such as neonatal infant mortality, stunting, and infectious diseases, which require optimization of health programs. This research uses a descriptive qualitative approach with a document study method to analyze official documents related to the HDI in the health dimension of Kediri City. Data is integrated thru document analysis of annual HDI reports, regional development planning documents, and health statistics data from 2019-2023. Data analysis was conducted inductively to identify patterns and relationships between programs. The life expectancy in Kediri City reached 75.74 years in 2023. There are three main challenges: 13 cases of neonatal infant deaths, 784 stunted children under five, and a high number of infectious diseases (201 HIV, 1,379 TB). Strategic programs implemented include The Movement to Reduce Maternal and Infant Mortality (GEMAKIBA), high-risk pregnant women visits, Posyandu for the Life Cycle, and disease prevention programs. Optimizing health programs thru an integrated approach that is promotive, preventive, and curative has proven effective in increasing the Human Development Index (HDI). The sustainability of the program and the strengthening of the monitoring and evaluation system are key to maintaining the positive trend of sustainable human development.